Impact of weather factors on traffic conditions and road safety: a case study of Pan Island Expressway in Singapore - Sim, Jack Jia Jing (Nanyang Technological University, 2023)
This study examines the relationship between weather factors (rainfall, temperature, and wind speed) and the speed bands of vehicles on the Pan Island Expressway in Singapore during peak morning traffic hours. Using data from June, July, August, September, and December 2022, the analysis focuses on different road categories and conducts separate or combined month analyses. Traffic data was collected from the Land Transport Authority (LTA) DataMall, and weather data was acquired from Data.gov.sg. Multiple linear regression was performed to investigate the relationships between weather factors and average speed across different road categories. The findings reveal that weather factors have limited explanatory power for average speed variations across different road categories, with weak correlations between average speed and weather factors. The R-squared values range from 0.5% to 14.5%, indicating that other factors not considered in this analysis might have a more significant impact on average speed. Further research is required to develop a more comprehensive understanding of the determinants of average speed on various road categories. This study contributes to the literature on the complex relationship between weather factors and road safety, informing traffic management strategies, road safety initiatives, and urban planning efforts.